Alterations in autonomic cardiac modulation in response to normobaric hypoxia. Issue 8 (16th November 2016) - Giles, David; Kelly, John; Draper, Nick
Abstract: Purpose : The present study aimed to determine if autonomic cardiac modulation was influenced by acute exposure to normobaric hypoxia. Method : Ten healthy male lowland dwellers completed five block-randomised single-blinded, crossed-over acute exposures to a normobaric hypoxic environment, each separated by 24 hours' recovery (20.3%, 17.4%, 14.5%, 12.0% and 9.8% FI O2 ). Supine recordings were made of arterial oxygen saturation and electrocardiogram (ECG). RR intervals from the ECG trace were analysed for time (SDNN, lnrMSSD), frequency (lnVLF, lnLF, lnHF, lnTP, LFnu, and HFnu), and nonlinear (DFA- α 1 and SampEn) heart rate variability components. Results : A significant reduction in arterial SaO2 occurred with reduced FI O2, along with a rise in heart rate (Cohen's d  = 1.16, 95% Confidence Interval [2.64–6.46]), significant at 9.8% FI O2 . A decrease in autonomic cardiac modulation was also found as shown by a statistically significant (at 9.8% FI O2 ) decrease in lnTP ( d  = 1.84 [1.74–1.94]), and SampEn ( d  = 0.98 [0.83–1.12]) and an increase in DFA- α 1 ( d  = 0.72 [0.60–0.84]) from normoxia at 9.8% FI O2 . Conclusion : The decrease in variability indicated a reduction in autonomic cardiac modulation. There appears to be a threshold ∼9.8% FI O2 (∼6000 m equiv.), below which significant alterations in autonomic control occur.